Identificationof Y Ang Factor Affects Level of Parental Anxiety Towards Covid 19 Vaccination in Children - Ika Rizki Anggraini; Nurul Aini (Universitas Malahayati Lampung, 2023)
ABSTRACT The covid 19 virus has affected children, and adolescents and children now account for more than a fifth of new cases in parts of the world. Vaccination is carried out from all ages, including children over 6 years old. But the challenge is about how parents can vaccinate their children. This is important to do because parents are the key in all decision-making determinants in children. In addition, this study is important to be carried out as an evaluation material in achieving the coverage of the covid 19 immunization target in children. The purpose of this study was to identify actors who influenced the level of parental anxiety towards covid 19 vaccination in Children. This research method uses descriptive analysis with a cross sectional study approach. The population and sample are parents who have children aged 6-18 years. This study used an accidental sampling method with the number of 30respondents of parents who had children aged 6-18 years. The research sites are located in several elementary schools in the Malang city area that have carried out covid 19 vaccinations. The results of this study showed that the age of 50 years old parents, namely 16 people (53.3%), of which 18 people (60%) did not experience anxiety. Ibu household (IRT) which was 17 respondents (56.7%) with a mild anxiety level of 5 people, respondents were dominated by those with 2 children, namely 21 people (70%) consisting of 4 people experiencing severe anxiety. Conclusion: The results show that parents who have psychological factors are related to the level of parental anxiety towards covid 19 vaccination in children. Keywords: Covid-19, Anxiety, Parents, Vaccination in Children